Timing and Amplitude of Light Exposure, Not Photoperiod, Predict Blood Lipids in Arctic Residents: A Circadian Light Hypothesis - Denis Gubin; Sergey Kolomeichuk; Konstantin Danilenko; Oliver Stefani; Alexander Markov; Ivan Petrov; Kirill Voronin; Marina Mezhakova; Mikhail Borisenkov; Aislu Shigabaeva; Julia Boldyreva; Julianna Petrova; et al. (Biology)
In Arctic residents, blood lipids fluctuate seasonally in response to changes in light exposure (LE) patterns. This study investigates which aspects of LE (timing, dynamic range, and duration) are related to lipid profiles. We analyzed actigraphy data measuring LE and blue light exposure (BLE) along with blood determinations from 27 residents across different seasons. We assessed circadian parameters of melatonin in a subset of participants. We found that features of BLE and melatonin significantly predicted lipids: An earlier BLE acrophase was associated with higher HDL-C (β = −0.246, p = 0.013). Nighttime BLE was positively associated with TC (β = 0.290, p = 0.008) and LDL-C (β = 0.253, p = 0.025). The normalized circadian amplitude of BLE was inversely associated with the TG/HDL ratio (β = −0.384, p < 0.001). Finally, earlier melatonin was associated with lower TG/HDL (β = 0.464, p = 0.007). Results remained significant after adjusting for co-factors of photoperiod duration, age, sex, and indigeneity. These findings suggest that patterns of LE (circadian light hygiene) could be a way to improve cardiovascular health.